Market Reaction to Mandatory Nonfinancial Disclosure - Grewal, Jody; Riedl, Edward J.; Serafeim, George (Management Science, 2019)
We examine the equity market reaction to events associated with the passage of a directive in the European Union (EU) mandating increased nonfinancial disclosure. These disclosures relate to firms’ environmental, social, and governance (ESG) performance, and would be applicable to firms listed on EU exchanges or with significant operations in the EU. We predict and find (i) an average negative market reaction of –0.79% across all firms, (ii) a less negative market reaction for firms having higher predirective nonfinancial performance, and (iii) a less negative reaction for firms having higher predirective nonfinancial disclosure levels. In addition, results are accentuated for firms having the most material ESG issues, as well as investors anticipating proprietary and political costs as a result of the mandated disclosures. Finally, we find that the negative market reaction is concentrated in firms with weak preregulation ESG performance and disclosure, which exhibit an average return of –1.54%; in contrast, firms with strong preregulation disclosure and performance exhibit an average positive return of 0.52%. Overall, the results are consistent with the equity market perceiving net costs (benefits) for firms with weak (strong) nonfinancial performance and disclosure around key events surrounding the mandatory disclosure regulation of nonfinancial information. This paper was accepted by Shiva Rajgopal, accounting.